(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The physicochemical quality of drinking waters of 6 sources from Talakaveri river and different parts of NMAMIT campus( Nitte-Udupi distic) was studied. Drinking water sample was first taken from the filtrate after the water was led into the filter.Second water sample was taken from tap. Ground water sample was taken from well and other three samples were taken from lake, falls and river. The physicochemical quality of drinking water was affected by the origin of raw water. The quality goal was exceeded by all drinking water samples. In general, the physicochemical quality of drinking waters from different sources were rather similar.This project is based on analysis of physical, chemical quality of different water samples. The water samples were collected from different sources. The purpose of our study is to bring an awareness regarding portability of water among people. We can also develop new techniques to eradicate water borne diseases and new equipment’s to prevent water pollution from our studies. The water samples were collected during rainy season in the month of June and July of the year 2018. The parameters used to analyse the quality of water is also called as water quality index. The major properties analysed are as follows: Taste and Odour, Colour, Temperature,Total dissolved solids, Total suspended solids, Determination of pH, Conductivity and Turbidity.